Benefits of Social Contact in Individuals With Psychotic Symptoms: Do Closeness of the Contact and Empathic Skills Make the Difference? - Krijnen, Lisa J. G.; Lemmers-Jansen, Imke L. J.; Fett, Anne-Kathrin J.; Krabbendam, Lydia (Frontiers in Psychology, 2021)
Objectives: Social contact is known to be beneficial for humans’ mental health. Individuals with psychotic symptoms (PS) tend to show poorer social and interpersonal functioning. However, in this patient population, social contact may be crucial for their mental wellbeing and treatment success. However, closeness of social contact (familiar versus less familiar others), rather than only the presence or absence of social contacts, may play an important role. Empathy may heighten the beneficial effects of social/close contact on mental health, facilitating interactions. We investigated the association between social contact and closeness of contact on mental health, defined as positive symptoms, positive affect and negative affect in PS and control participants, with empathy as a moderator. Methods: Participants were 16-30 years old. Information regarding social/close contact and mental health were obtained using the Experience Sampling Method in individuals with PS (n = 29) and healthy controls (n = 28). Empathy was measured using a questionnaire. Results: Social contact was associated with higher positive affect in the total sample. Contact with close as opposed to less close contacts was related to better mental health: it was associated with lower positive symptoms in the PS group, and with more positive affect in the total sample. Empathy moderated the association between closeness of contact and positive affect in the total sample, in which the combination of higher levels of empathy combined with the presence of close contact was associated with higher positive affect in the total sample. However, the direct association between empathy and positive affect was not significant per group of contact. Conclusion: The results suggest that social contact, but especially contact with a close other is important for mental health outcomes: Contact with close others is beneficial for positive affect in the total sample and for positive symptoms in individuals with PS.